2018
DOI: 10.1007/s11664-018-6394-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of a p–n Heterojunction of Li-Doped NiO and Al-Doped ZnO for Thermoelectrics

Abstract: The electrical properties of a p-n heterojunction of polycrystalline p-type Ni0.98Li0.02O and n-type Zn0.98Al0.02O have been investigated for potential applications in high-temperature oxide-based thermoelectric generators without metallic interconnects. Current-voltage characteristics of the junction were measured in a two-electrode setup in ambient air at 500 -1000 °C. The resistance and rectification of the junction decreased with increasing temperature. A non-ideal Shockley diode model was used to fit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Figure b shows the replot of the J – V curve in the semilogarithmic mode for the heterojunctions, and the ideality factor is found to be ≈1.1. Since the ideality factor is close to unity, the electrical transport of the junctions is dominated by diffusion current, where recombination processes are minor. , Furthermore, the diode characteristics of the present device are improved when compared with the ones presented by Chavez et al , and Desissa et al in their bulk devices with a p–n junction without metal contact. Particularly, Chavez et al reported an inhomogeneous p–n junction due to the mixing of the nanoparticle powders prior to and during the densification step for the device fabrication.…”
Section: Results and Discussionmentioning
confidence: 53%
“…Figure b shows the replot of the J – V curve in the semilogarithmic mode for the heterojunctions, and the ideality factor is found to be ≈1.1. Since the ideality factor is close to unity, the electrical transport of the junctions is dominated by diffusion current, where recombination processes are minor. , Furthermore, the diode characteristics of the present device are improved when compared with the ones presented by Chavez et al , and Desissa et al in their bulk devices with a p–n junction without metal contact. Particularly, Chavez et al reported an inhomogeneous p–n junction due to the mixing of the nanoparticle powders prior to and during the densification step for the device fabrication.…”
Section: Results and Discussionmentioning
confidence: 53%